2009
DOI: 10.2174/1876396000902010092
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals and Nutraceutical Supplementation Criteria in Cancer: A Literature Survey

Abstract: Nutraceuticals are natural and bioactive products with food value to keep energy balance in the body and promise substantial therapeutic value in several diseases. Major nutraceuticals are now part of nutrition supplements at nonprescription counters and their self-prescription is increased at large scale. The current literature suggests the nutraceutical use in most of cancer prevention and management. The biochemical mechanism of nutraceuticals is poorly reported and most of the literature indicates the succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 162 publications
(185 reference statements)
0
8
0
Order By: Relevance
“…their anticancer effect and came with promising results. Naturaceuticals such as silibinin, quercetin, curcumin [13][14][15] and plant extracts such as Curcuma longa, Moringa oleifera, Camellia sinensis, Dictyopteris undulata have also been tested for their anticancer effects against colon cancer. [16][17][18][19] In previous studies C. fimbriata has been evaluated against several cancer models except colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…their anticancer effect and came with promising results. Naturaceuticals such as silibinin, quercetin, curcumin [13][14][15] and plant extracts such as Curcuma longa, Moringa oleifera, Camellia sinensis, Dictyopteris undulata have also been tested for their anticancer effects against colon cancer. [16][17][18][19] In previous studies C. fimbriata has been evaluated against several cancer models except colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A vegetarian diet can even foster weight loss [17]. LPC can be used as a dietary supplement which acts as a health promoting and disease preventing nutraceutical [7].…”
Section: Reversal Of Immunogenicity Of Hepatitis B Antigen By Treatmentmentioning
confidence: 99%
“…Leaves are also a good source for protection against neoplastic, cardiovascular disorders and immune deficiency. Studies on animals revealed that leaves of the plant have anti-tumoural activity and strong mutagenic activity [5,6] therefore the leaves of the plant can be used as a nutraceutical that demonstrate specific health or medical benefits including the prevention and treatment of disease beyond basic nutritional functions [7]. The whole plant (leaf and stem) is used as cattle fodder to improve milk production.…”
Section: Introductionmentioning
confidence: 99%
“…A simple plan of anticancer formula is suggested for herbiceutical mixture including active biochemicals, herbs, roots in suitable carrier for cancer therapeutics: Recently, the safe use of nutraceuticals and nutraceutical supplementation formula was reviewed by author with major focus on preclinical and clinical evidences and role of regulatory federal governments on bioactive foods, herbs and use of nutraceuticals [69].…”
Section: Anticancer Herbiceutical Formulamentioning
confidence: 99%